A PARAPHRASING STRATEGY INSTRUCTION MODEL TO HELP UNIVERSITY STUDENTS AVOID PLAGIARISM IN ACADEMIC WRITING - Thohir, Lalu; Nurtaat, Lalu; Udin, Udin; Isnaini, Mh. (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2023)
ABSTRACTA paraphrasing strategy instruction model has been developed through a research and development method. The developed model is called the 3RI (Read, Rewrite, Revise, Integrate) paraphrasing strategy instruction model. This is a part of the research and development, which is aimed at evaluating the effectiveness of the developed model. For evaluation, the field testing was carried out in the English study program at the University of Mataram. Seventy-five students who were taking academic writing courses were involved in this study. To evaluate the effectiveness of the developed model, the students self-assessed before and after having been treated using the 3RI paraphrasing strategy instruction model. After the treatment, the students were asked to fill in the questionnaire, which covered statements about the students' responses toward the instruction with the developed model. The results indicated a significant difference between the student's scores in the self-assessment before and after the treatment. Further, the students generally responded positively to the treatment with the developed model. The 3RI paraphrasing strategy instruction model can be one of the ways to help students avoid plagiarism and develop their creativity and critical thinking skills. ABSTRAKSebuah model instruksi strategi perparafiran telah dikembangkan melalui metode penelitian dan pengembangan. Model yang dikembangkan disebut sebagai model instruksi strategi perparafiran 3RI (Read, Rewrite, Revise, Integrate). Ini merupakan bagian dari penelitian dan pengembangan yang bertujuan untuk mengevaluasi efektivitas model yang dikembangkan. Untuk evaluasi, uji lapangan dilakukan di program studi bahasa Inggris di Universitas Mataram. Tujuh puluh lima mahasiswa yang mengikuti mata kuliah penulisan akademis terlibat dalam penelitian ini. Untuk mengevaluasi efektivitas model yang dikembangkan, mahasiswa melakukan penilaian diri sebelum dan setelah menerima perlakuan menggunakan model instruksi strategi perparafiran 3RI. Setelah perlakuan, mahasiswa diminta untuk mengisi kuesioner yang mencakup pernyataan tentang tanggapan mahasiswa terhadap instruksi dengan model yang dikembangkan. Hasilnya menunjukkan perbedaan signifikan antara skor penilaian diri mahasiswa sebelum dan setelah perlakuan. Selanjutnya, mahasiswa umumnya memberikan tanggapan positif terhadap perlakuan dengan model yang dikembangkan. Model instruksi strategi perparafiran 3RI dapat menjadi salah satu cara untuk membantu mahasiswa menghindari plagiarisme dan mengembangkan kreativitas serta keterampilan berpikir kritis mereka.How to Cite: Thohir, L., Nurtaat, L., Udin, & Insaini, M. (2023). A paraphrasing strategy instruction model to help university students avoid plagiarism in academic writing. IJEE (Indonesian Journal of English Education), 10(2), 340-354. https://doi.org/10.15408/ijee.v10i2.34750